Model Kepemimpinan Visioner Kepala Madrasah dalam Penguatan Inovasi Pembelajaran di MI PAS Baitul Qur'an Gontor - Achmadi, Nur; Sulton, Sulton (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
This study aims to analyze the visionary leadership model of the madrasah principal in strengthening learning innovation at MI PAS Baitul Qur’an Ponorogo. The research employed a descriptive qualitative approach with a case study strategy. Data were collected from the madrasah principal, teachers, and curriculum-related documents through participatory observation, in-depth interviews, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing.The findings reveal that the visionary leadership model is manifested through three main components: the formulation of a Qur’anic-progressive vision, participatory communication of the vision, and the implementation of the vision through learning innovations. This leadership model encourages teacher capacity development, the use of educational technology, and the implementation of a flexible curriculum grounded in pesantren values. Moreover, the madrasah principal effectively manages resistance to change and builds collaboration with stakeholders to support sustainable learning innovation. The study concludes that visionary leadership plays a significant role in fostering an innovative, adaptive, and Qur’anic madrasah culture, while positively influencing students’ learning motivation and teachers’ professionalism. This model may serve as a reference for leadership development in similar Islamic educational institutions.